Aspects of Personal Data Protection According to International Law - Ade Rizki Saputra (PT FORMOSA CENDEKIA GLOBAL, 2023)
This journal investigates aspects of personal data protection in the context of international law. With the development of information technology and globalization, cross-border exchange of personal data has become commonplace. However, the challenge that arises along with this is how to protect individual personal data from potential misuse by various parties, including the state and private companies. This journal describes developments in international law related to personal data protection, including key legal instruments such as the Council of Europe Convention on Human Rights and the Protection of Personal Data, as well as the role of international organizations such as the United Nations in addressing this issue. This research also highlights the differences in approaches that exist in various countries in regulating personal data protection. In addition, this journal reviews the practical challenges of implementing personal data protection principles in a global context, including issues of data security, cross-border transfer of data, and comparison of applicable regulations in various jurisdictions. Furthermore, this journal evaluates the impact of personal data protection policies on international trade, technological innovation, and human rights. This research provides in-depth insight into the complexity of personal data protection issues in international law and the importance of global regulatory harmonization to maintain a balance between individual protection and technological developments